2013
DOI: 10.1016/s0972-6292(16)30668-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technique of Dual Chamber Pacing Through Minithoracotomy and Transatrial Endocardial Active Fixation Lead Insertion for Epicardial Pacing Lead Malfunction

Abstract: Epicardial pacing lead fixation is employed in patients with cavopulmonary anastamosis (Glenn shunts) when they need permanent pacing. Epicardial pacing in these patients may malfunction due to high pacing thresholds or diaphragmatic pacing. A novel technique of transatrial insertion of two endocardial screw-in pacing leads through right anterolateral minithoracotomy could achieve synchronous atrioventricular pacing in a patient with Ebsteins anomaly with symptomatic sinoatrial and atrioventricular nodal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…When superior vena cava is occluded following Senning or Mustard surgery, stenting of the vein provides the access for an endocardial lead [32]. Hybrid peratrial approach described in section 2.2 has also been advocated in such patients [33,34]. Peratrial approach is safe, less morbid, offers low pacing threshold and can be applied widely with few contraindications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When superior vena cava is occluded following Senning or Mustard surgery, stenting of the vein provides the access for an endocardial lead [32]. Hybrid peratrial approach described in section 2.2 has also been advocated in such patients [33,34]. Peratrial approach is safe, less morbid, offers low pacing threshold and can be applied widely with few contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…Peratrial approach is safe, less morbid, offers low pacing threshold and can be applied widely with few contraindications. Peratrial lead placement has the additional advantage to allow somatic growth by creating a smaller redundant atrial lead loop [34]. Venous collaterals representing remnants of persistent left superior vena cava may develop after Fontan surgery and allow access to the coronary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial lead option was also ruled out owing to their complication rates and non MRI compatibility. Transatrial lead placement was also not indicated [ 10 , 11 ]. Cardiopulmonary bypass was not used in this case.…”
Section: Case Reportmentioning
confidence: 99%
“…This result was difficult to analyze owing to the small number of cases (n ¼ 12) and different techniques that were used in performing TML-V (transatrial or transventricular). Literature on TML-V placement exists only as small series or case reports without long-term follow-up [12][13][14]. Kassai and colleagues [14] reported transapical placement of ventricular pacing leads for adult cardiac resynchronization therapy in 20 patients.…”
Section: Commentmentioning
confidence: 99%